Participation in the International Judo Federation World Tour competitions and performance in Tokyo Olympic Games - Santos, Danilo F. C.; Kons, Rafael L.; Lopes-Silva, João P.; Agostinho, Marcus F.; Detanico, Daniele; Takito, Monica Y.; Franchini, Emerson (Frontiers in Sports and Active Living, 2023)
The International Judo Federation introduced a ranking system in 2009 that determines top athletes for the Olympic Games and seeds them in competitions. Previous research indicated that this ranking list and past performances predicted 19-27% of performance in the Olympic Games and World Championships. However, due to the COVID-19 pandemic, the relationship between Judo World Tour competitions and Olympic Games performance may have been affected. This study aimed to examine the relationship between athletes' performance in Judo World Tour competitions and their competitive performance at the Olympic Games. Data from 393 athletes who participated in the Tokyo Olympics were analyzed considering both long and short-term performance measures. Pearson correlation was used to determine the relationship between variables and multiple linear regressions were used to predict performance for each sex and the entire sample. The results revealed a range of magnitudes in the correlation between variables, varying from small to large. In terms of regression analyses, it was observed that, for females, the percentage of matches won during the classification period and competition in the year prior to the Olympic Games predicted 37% of their performance. For males, the percentage of matches won during the classification period and competition in the six months before the Olympic Games predicted 36% of their performance. Thus, athletes' quality and reduced